Clinical case of endo-periodontal defeat of the first maxillary molar in peadiatric dentistry - G. R. Ruvinskaya; E. V. Kuzmenko; Z. I. Yarulina (Эндодонтия Today, 2019)
In the practice of a dentist, a clinical situation occurs where the inflammatory processes are to varying degrees determined both in the periodontium and in the pulp of the tooth. A clinical case of endo-periodontal lesion in a 10-year-old child in the area of the upper first molar is described, which presents a difficult task, both in terms of diagnosis and treatment. The diagnostic value of CBCT was noted.